"The Sun Is the Poor Mayo's Cobija": Mayo Weavers Encounter Neoliberalism - Yetman, David (Anthropologica, 2022)
Mayo women of southern Sonora, Mexico have woven textiles for centuries. We undertook a study of contemporary Mayo weavers to determine the state of Mayo weaving, its significance to the homes and communities in which weaving is done, and its future prospects. We also wished to ascertain whether or not Mayo weaving is in a state of precipitous decline, as we had heard anecdotally from numerous sources, or in a state of expansion, as predicted by Burns (1979). Mexico's adoption of neoliberal economic policies within the last two decades has affected weavers. The isolation of Mayo weavers in an environment of increased organization of the Mexican economy along capitalist lines makes them an anomaly. Although weavers control the entire process and marketing of their cobijas and serapes, they lack support of government agencies and alternative trade organizations in facilitating the purchase, advertisement and sales of their textiles. Although the women face difficulties, they view weaving as fundamental to their identity, an important Mayo tradition they hope will be perpetuated.